Analysis of Factors That Influence the Occurrence Of Corruption in the Perspective of Fraud Hexagon - Tiara Setra Linuhung; Rozmita Dewi Yuniarti (Britain International for Academic Research (BIAR) Publisher, 2023)
Fraud is a term that is often found in revealing frauds, both in the private and public sectors. The Association of Certified Fraud Examiners (ACFE), which is an anti-fraud organization, defines fraud as an unlawful act committed intentionally for personal or group gain and can harm other parties. ACFE categorizes fraud into three categories, namely corruption, misuse of assets, and financial statement fraud. Corruption, especially in the public sector, has become a familiar issue among the public because it is also related to the public's demand for transparency of public information. This study uses a quantitative research design with a causal associative approach. The data sources used in this study are the BPK Audit Report (LHP), the website of each provincial government, and KPK report data. The results of this study indicate that stimulus, collusion, and ego have a positive and significant influence so that the central government must provide more supervision for provincial governments that are financially independent, have high capital expenditurerealization, and provide a rejection response to the BPK audit results